Enforcement of housing law in Malaysia: issues and challenges - Amin, Naemah; Syed Abdul Kader, Sharifah Zubaidah; Kassim, Salina (2015)
Due to the significant nature of private housing project to public at large, housing developments in Malaysia is governed by stringent laws and regulations with the main purpose of protecting the interests of buyers. Despite the existence of these legal instruments, complaints on housing-related problems remain one of major consumers' complaints in Malaysia for the past many years. This includes complaints relating to abandoned project, late delivery of vacant possession, low quality material and workmanship, lack of basic amenities etc. In addition to the system of 'sell then build' that is commonly blamed for causing those problems, the question also arises as to whether the laws have been effectively implemented and enforced. The study aims to assess the existing enforcement mechanisms in housing industry which may be derived from private, public, administrative and self-regulations initiatives. The focus is to identify the adequacy and weaknesses of each mechanism in achieving a high degree of compliance possibly at lowest cost. The study also highlight challenges posed in implementing and enforcing housing development regulations. Ultimately, the study hopes to shed light on further improvements of the enforcements efforts which can enhance the effectiveness of legal measures in regulating the housing industry and safeguarding the interest of house buyers.